THE ANALYSIS OF UNDERGRADUATE STUDENTS"™ RESEARCH PROPOSALS DURING THE PANDEMIC ERA (A Descriptive Research in Language Education Study Program of FKIP UNTAN in the Academic Year of 2020 to 2021) - Damara, Kevin; Salam, Urai (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
This research aims to see the trend during the pandemic on what undergraduate students choose a title for their research proposal and to identify the phenomenon on it. The method in this research is descriptive research. The research was conducted by gathering titles from March 2020 until December 2021 with 140 titles. By conducting the descriptive research with analysis, it was found that students who chose four language skills as their category of research were 39%,   language elements were 21%, teaching and learning 30%, English literature 10%, and English linguistic 0%. It was found that 40% of students chose descriptive research as their method of writing a research proposal. Most students chose development research with 21%. 16% of students chose action research. 14% of students chose case study research. 4% of the students chose pre-experimental research. 5% of students chose another method instead of those mentioned methods. In other words, many students chose descriptive research as their method to conduct a research proposal in the pandemic era.